ASSOCIATION OF POLYCYSTIC OVARY SYNDROME AND THYROID DYSFUNCTION AMONG REPRODUCTIVE WOMEN: A CROSS-SECTIONAL STUDY - ANEBARACY V; NAVEEN KUMAR C; NAVEEN RAVI; NITHYA RAJAPANDIAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Polycystic ovarian syndrome (PCOS) is became most common problem in the reproductive age group women who seem to be adversely affected by associated thyroid dysfunction. Ovarian failure and pregnancy-related complications leaded by both factors. The study helps to explore the incidence and etiology of diverse thyroid conditions among PCOS individuals. Methods: This prospective single‑center study with 40 female patients with hyperandrogenism, hirsutism, oligo‐anovulation, and polycystic ovaries patients were defined as having PCOS according to the revised 2003 Rotterdam criteria and Ferriman–Gallwey score with comprised the study population. Normal female subjects were studied as the control population who had normal thyroid function and without PCOS. By measuring of serum thyroid-stimulating hormone (TSH), free thyroxine levels (free T3 and free T4), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estrogen, progesterone, and testosterone can evaluate thyroid function. Along with ultrasound was performed to confirm the PCOS. By SPSS version 19 Chi-square test and t-test were determined. Results: This case–control study revealed that a statistically significant higher prevalence of PCOS patients was found to have higher mean TSH values that were 5.33±2.51 μIU/mL, the mean for T3 and T4 was 154±138 μg/dL and 11.27±8.47 μg/dL, respectively. The mean FSH values were 07.27±4.49 μIU/mL, the mean LH was 84.27±38.49 μIU/mL, the mean estrogen 342±202 pg/mL, the mean progesterone values were 14.2±8.9 ng/mL and the mean testosterone levels were 69.73±9.28 ng/mL. Conclusion: Thyroid dysfunction shows a high prevalence in PCOS patients. Dysfunction can be treated which helps to manage infertility associated with PCOS.